Political patronage and political values: The developmental role of political patronage and its impact on shaping political values in rural Uganda. - Titeca, Kristof (Afrika Focus, 2006)
This article points out the importance of neo-patrimonial theories in understanding local socio-political dynamics. Through the analysis of a case study in Western Uganda, it is firstly shown how within ’formal’ state institutions, there is an ’informal’ logic of competing political camps. These political camps, and their subsidiary networks of political patronage, have adverse effects for development. Secondly, this system has a profound impact on how people perceive the service- delivery functions of the state: people on the ground do not expect the state to be there for everyone, but only for the people of their ’political camp’ or network. Also the role of the state is seen as strongly personalised, as the ’big men’ are perceived to have taken over the service provision activities of the state. Key Words: Local Government, Neo-Patrimonialism, Patronage, Uganda, Service-Provision